The North American Neuroendocrine Tumor Society Consensus Guidelines for Surveillance and Medical Management of Pancreatic Neuroendocrine Tumors. Issue 7 (August 2020) - Halfdanarson, Thorvardur R.; Strosberg, Jonathan R.; Tang, Laura; Bellizzi, Andrew M.; Bergsland, Emily K.; O'Dorisio, Thomas M.; Halperin, Daniel M.; Fishbein, Lauren; Eads, Jennifer; Hope, Thomas A.; Singh, Simron; Salem, Riad; et al.
Abstract : Abstract: This article is the result of the North American Neuroendocrine Tumor Society consensus conference on the medical management of pancreatic neuroendocrine tumors from July 19 to 20, 2018. The guidelines panel consisted of medical oncologists, pathologists, gastroenterologists, endocrinologists, and radiologists. The panel reviewed a series of questions regarding the medical management of patients with pancreatic neuroendocrine tumors as well as questions regarding surveillance after resection. The available literature was reviewed for each of the question and panel members voted on controversial topics, and the recommendations were included in a document circulated to all panel members for a final approval.